A control method for the single-phase three-leg unified power quality conditioner without a phase-locked loop - Feng, Depin; Chen, Tao; Zhang, Liang; Meng, Weiqi; He, Jinwei (Frontiers in Energy Research, 2024)
The single-phase three-leg unified power quality conditioner (UPQC) can achieve functions of voltage compensation, reactive power compensation, and harmonic compensation. However, traditional control algorithms require a phase-locked loop to obtain real-time phase angle of the grid voltage, which undoubtedly increases algorithm complexity. To simplify the phase-locked calculation, this paper proposes a control method without phase-locked loop for the single-phase three-leg UPQC. In the proposed scheme, the instantaneous value of the grid voltage is employed to realize the grid integration control. Then, the load voltage reference is calculated in real-time using a second-order generalized integrator. Moreover, a simple algorithm for reactive power and harmonic compensation is discussed, further simplifying the control algorithm. Finally, a small-scale experimental platform is built, and the effectiveness of the proposed method is verified by the experimental results.